Oxazine-thione-based Colorimetric Fluorescent OFF-ON Probes for Hg2＋ Recognition - 张欠欠 孙如 葛健锋 徐庆锋 李娜君 路建美 (Chinese journal of chemistry, 2011)
Two colorimetric probes based on oxazine-thione la and lb for the detection of Hg2＋ were designed and synthesized. The probe la exhibits about a 70-fold enhancement in fluorescence and a color change alter the addition of Hg2＋ in acetonitrile/wate solvent, la was also highly selective to Hg2＋ over other metal ions. Furthermore, DFT/TDDFT calculations were taken to explain the OFF-ON emission response.